COVID-19–associated delayed-onset MuSK-positive myasthenia gravis presenting solely with respiratory failure: a case report - Cao, Xiao-Guang; Ni, Jun-xi; Zhu, Xiong-feng; Meng, Hua-dong; Huang, Chong-jian (Frontiers in Immunology, 2025)
BackgroundMuscle-specific kinase (MuSK) myasthenia gravis is a rare autoimmune disorder of the neuromuscular junction that predominantly affects the bulbar and respiratory muscles. Although SARS-CoV-2 infection has been implicated as a precipitating factor, post-COVID-19 MuSK-MG remains exceedingly uncommon.Case presentationA 29-year-old woman with a six-year history of unexplained exertional dyspnea was hospitalised twice for acute hypercapnic respiratory failure. The first episode, five months earlier, was attributed to severe tricuspid regurgitation; the second occurred eight weeks after mild COVID-19 and was characterized by coma due to hypercapnic respiratory failure without parenchymal lung disease.DiagnosisStandard electrophysiology, neostigmine testing and acetylcholine-receptor antibodies (AChR-Ab) were negative. Given persistent ventilator dependence, MuSK antibodies (MuSK-Ab) were measured and found strongly positive.InterventionsThe patient underwent five plasma-exchange sessions, then received oral prednisone (50 mg day), tacrolimus (1.5 mg q12h) and nebulized salbutamol.OutcomesShe was weaned from non-invasive ventilation by day 23, discharged on day 27 (mMRC grade I) and remained stable on low-dose prednisone/tacrolimus at three-month follow-up.ConclusionSARS-CoV-2 infection may plausibly act as a trigger for late-onset MuSK-MG presenting as isolated hypercapnic respiratory failure. In otherwise unexplained weaning failure, neuromuscular-junction disease should be considered even without limb or ocular weakness. Early antibody testing and prompt immunomodulatory therapy [plasma exchange (PLEX) plus glucocorticoid/tacrolimus] may be life-saving and yield rapid recovery.